Pemphigus Disease: A geoepidemiologic preliminary study in Iran - Azimi, Somayyeh; Taheri, Jamileh Beigom; Namazi, Zahra; Bakhtiari, Sedigheh; Rafieian, Nasrin (Journal of Dental School, 2019)
Objectives Pemphigus is an autoimmune, life-threatening, blistering disease. Knowledge about the epidemiology of this disease however, is still limited. The aim of this study was to investigate the frequency and geographic distribution of pemphigus patients in Iran. Methods Medical records of patients with definitive diagnosis of pemphigus disease during a seven-year period from March 2006 to March 2013 were retrospectively reviewed. All individuals were classified based on geographical aspects. Results A total of 110 patients (59 females and 51 males) with an average age of 46.5 ± 13.6 for the females and 45.8± 12.5 for the males were evaluated. Male patients were slightly younger than female patients, but the difference was not statistically significant. Also, there was no significant association between age and the year of frequency. The most frequent type of pemphigus was the vulgaris type (93.6%). On the base of climate, the highest frequency was seen in the Moderate to severe internal (very hot) desert area and the humid and temperate climates (Caspian). There was no significant difference between the mean ages of pemphigus patients in the four geographic regions, (P value=0.421). Based on altitude in each climatic region, less than 10% of patients were from high altitude areas. Conclusion Environmental factors are important in frequency of autoimmune disease including pemphigus. We concluded that the frequency of pemphigus disease might be different in different climates and altitude. Further research towards the improvement of data on the geographical study could open up a field to identify the patterns of pemphigus disease